High‐value transitional care: translation of research into practice. Issue 5 (16th March 2011) - Naylor, Mary D.; Bowles, Kathryn H.; McCauley, Kathleen M.; Maccoy, Maureen C.; Maislin, Greg; Pauly, Mark V.; Krakauer, Randall
Abstract: Objective  To evaluate the impact of translating into a large US health plan, the Transitional Care Model (TCM), an evidence‐based approach to address the needs of chronically ill older adults throughout acute episodes of illness. Methods  A prospective, quasi‐experimental study of 172 at‐risk Aetna Medicare Advantage members in the mid‐Atlantic region who received the TCM. A baseline and post‐intervention (average of 2 months) comparison of enrolees' health status and quality of life was conducted. Member and physician satisfaction were assessed within 1 month post intervention. Health resource utilization and cost outcomes were compared to a matched control group of Aetna members at multiple intervals through 1 year. Results  Improvements in all health status and quality of life measures were observed post‐ intervention compared to pre‐intervention. Among 155 stringently matched pairs, a significant decrease in number of re‐hospitalizations (45 vs. 60, P  < 0.041) and total hospital days (252 vs. 351, P  < 0.032) were observed at 3 months. Reductions in other utilization outcomes or time points were not statistically significant. The TCM was associated with a short‐term decrease of $439 per member per month in total health care costs at 3 months and cumulative per member savings of $2170 at 1 year ( P  < 0.037). Conclusions  Findings demonstrate that a rigorously tested model of transitional care for chronically ill older adults can be successfully translated into a real‐world organization and achieve higher value.